Prognostic value of chromosomal imbalances, gene mutations, and BAP1 expression in uveal melanoma. Issue 8 (26th June 2018) - Patrone, Serena; Maric, Irena; Rutigliani, Mariangela; Lanza, Francesco; Puntoni, Matteo; Banelli, Barbara; Rancati, Silvia; Angelini, Giovanna; Amaro, Adriana; Ligorio, Paolo; Defferrari, Carlotta; Castagnetta, Mauro; et al.
Abstract: Uveal melanoma (UM) exhibits recurring chromosomal abnormalities and gene driver mutations, which are related to tumor evolution/progression. Almost half of the patients with UM develop distant metastases, predominantly to the liver, and so far there are no effective adjuvant therapies. An accurate UM genetic profile could assess the individual patient's metastatic risk, and provide the basis to determine an individualized targeted therapeutic strategy for each UM patient. To investigate the presence of specific chromosomal and gene alterations, BAP1 protein expression, and their relationship with distant progression free survival (DPFS), we analyzed tumor samples from 63 UM patients (40 men and 23 women, with a median age of 64 years), who underwent eye enucleation by a single cancer ophthalmologist from December 2005 to June 2016. UM samples were screened for the presence of losses/gains in chromosomes 1p, 3, 6p, and 8q, and for mutations in GNAQ, GNA11, BAP1, SF3B1, and EIF1AX . BAP1 protein expression was detected by immunohistochemistry (IHC). Multivariate analysis showed that the presence of monosomy 3, 8q gain, and loss of BAP1 protein were significantly associated to DPFS, while BAP1 gene mutation was not, mainly due to the presence of metastatic UM cases with negative BAP1 IHC and no BAP1 mutation detected by Sanger sequencing. Loss of BAP1 protein expression and monosomy 3 represent the strongest predictors of metastases, and may have important implications for implementation of patient surveillance, properly designed clinical trials enrollment, and adjuvant therapy.